Enhanced Polymer Solar Cells Embedded By Gold Encapsulated Silver Plasmonic Nanoparticles - Alkhalayfeh, Muheeb Ahmad Mousa (2022)
Organic semiconducting polymers are useful in several photonic applications due to their tunable optical and electronic properties and ease of fabrication. However, due to the short exciton diffusion length and low carrier mobility in polymer solar cells (PSCs), their power conversion efficiency (PCE) is comparably lower than their inorganic counterparts. Therefore, several strategies have been developed to enhance the PCE of PSCs. One of the strategies is the plasmonic effect, which has shown potential applications in PSCs’. The shape and size of nanoparticles (NPs) are important factors since they directly affect surface plasmonic resonance (SPR) and the incident light’s scattering. Therefore, this study introduces plasmonic effects into PSCs by incorporating Au@Ag durian-shaped NPs to improve their performance. The plasmonic durian-shaped Au@Ag NPs, which can be placed in the hole transport layer (HTL) of the PSC, scatter light into the active layer, thereby increasing the optical path length of the incident light, leading to higher absorption and short circuit current density (Jsc) of the PSCs. The size properties and surface morphology of the Au@Ag NPs were analyzed using field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM). The topography of the PSCs’ layers with and without Au@Ag NPs was investigated using atomic force microscopy (AFM). UV–Vis spectroscopy and current density–voltage (J-V) analysis were used to investigate the electrical performance of the fabricated PSCs.